EHRA expert consensus statement and practical guide on optimal implantation technique for conventional pacemakers and implantable cardioverter-defibrillators: endorsed by the Heart Rhythm Society (HRS), the Asia Pacific Heart Rhythm Society (APHRS), and the Latin-American Heart Rhythm Society (LAHRS). Issue 7 (15th July 2021) - Burri, Haran; Starck, Christoph; Auricchio, Angelo; Biffi, Mauro; Burri, Mafalda; D'Avila, Andre; Deharo, Jean-Claude; Glikson, Michael; Israel, Carsten; Lau, Chu-Pak; Leclercq, Christophe; Love, Charles J; et al.
Abstract: With the global increase in device implantations, there is a growing need to train physicians to implant pacemakers and implantable cardioverter-defibrillators. Although there are international recommendations for device indications and programming, there is no consensus to date regarding implantation technique. This document is founded on a systematic literature search and review, and on consensus from an international task force. It aims to fill the gap by setting standards for device implantation.